THE USE OF CARTOON STORY MAKER SOFTWARE IN TEACHING WRITING DESCRIPTIVE TEXT - Rangga Ramdhani (Universitas Galuh, 2021)
The study was aimed to investigate the implementation of Cartoon Story Maker Software in the classroom. To gain the data, the author employed a qualitative case study and the data were obtained through the observation, interview and questionnaire. The author concluded that, the teacher used Cartoon Story Maker Software well in the classroom. The teacher had a strong perceptions on using Cartoon Story Maker Software that the teacher could make a good situation to motivate the students in teaching writing descriptive text. The teacher also confirmed that the students enjoyed it and it was found that almost all students (75%) preferred to learn to write descriptive text using Cartoon Story Maker Software and 25% was the rest who did not. Finally, the author provides suggestions for English teacher who teach English and students who learn English that Cartoon Story Maker Software gives the contribution to the learning process, so that the interaction in the teaching and learning process runs smoothly. Keywords: cartoon story maker software, descriptive text, writing